Increased nuclear import characterizes aberrant nucleocytoplasmic transport in neurons from patients with spinocerebellar ataxia type 7 - Macopson-Jones, Joshua G.; Adams, Maile; Philippe, Julien; La Spada, Albert R. (Frontiers in Molecular Neuroscience, 2024)
IntroductionSpinocerebellar ataxia type 7 (SCA7) is an inherited neurodegenerative disorder characterized by cerebellar and retinal degeneration. SCA7 is caused by a CAG-polyglutamine repeat expansion in the ataxin-7 gene, which encodes a transcription factor protein that is a core component of the STAGA co-activator complex. As ataxin-7 protein regularly shuttles between the nucleus and the cytosol, we sought to test if polyglutamine-expanded ataxin-7 protein results in nuclear membrane abnormalities or defects in nucleocytoplasmic (N/C) transport.MethodsWe used SCA7 266Q knock-in mice and their wild-type (WT) littermate controls to assess nuclear membrane morphology and N/C transport. Additionally, induced pluripotent stem cells (iPSCs) from SCA7 patients were differentiated into neural progenitor cells (NPCs) and cortical neurons to measure nuclear import and export dynamics. The expression of nucleoporin POM121, a key regulator of N/C transport, was also analyzed in SCA7-derived NPCs.ResultsOur analysis revealed no significant differences in nuclear membrane morphology between SCA7 knock-in mice and WT controls, nor did we observe alterations in N/C transport within neurons from these mice. However, we documented significantly increased nuclear import in both NPCs and cortical neurons derived from SCA7 patient iPSCs. When we examined nuclear export function in SCA7 iPSC-derived cortical neurons, we noted a modest decrease that constituted only a trend. Furthermore, we identified a significant decrease in the expression of full-length POM121 in SCA7 NPCs.DiscussionOur results reveal evidence for altered N/C transport in SCA7. The reduction in POM121 expression suggests a potential mechanism underlying these transport abnormalities. Importantly, our data suggests the N/C transport defect in SCA7 is distinctly different from other related neurodegenerative disorders.